Pengaruh Ukuran Perusahaan, Likuiditas dan Profitabilitas Terhadap Keputusan Investasi Perusahaan - Muhammad Rakha Rafiansyah Rizq; Regina Jansen Arsjah (Economic Reviews Journal, 2026)
Investment decisions are a crucial aspect of corporate financial management as they play an important role in supporting business growth and sustainability. Differences in capital expenditure intensity among firms indicate the influence of internal factors on investment policies. This study aims to analyze the effect of firm size, liquidity, and profitability on investment decisions of energy sector companies listed on the Indonesia Stock Exchange (IDX). This research is grounded in Neoclassical Investment Theory, Pecking Order Theory, and Agency Theory. The study employs a quantitative approach with a causal research design. The data used are secondary data obtained from the annual financial statements of energy sector companies for the period 2020–2024. The sample was selected using a purposive sampling method, resulting in 150 observations. Data analysis was conducted using multiple linear regression. The results show that firm size and profitability have a positive effect on investment decisions, while liquidity has a negative effect. These findings indicate that asset capacity and the ability to generate profits play a more significant role in determining investment policies than short-term liquidity levels in energy sector companies in Indonesia.